Outcome of Pregnancy among HIV Infected Women: A Retrospective Cohort Study in a Tertiary Care Hospital in Bangalore, India - Dharmini Manogna; Shalini C Nooyi; Nandagudi S Murthy (Medsci Publications, 2017)
Background- HIV positive women have been reported to have a higher incidence of adverse pregnancy outcomes. Objectives- To determine the incidence of maternal and perinatal morbidity and mortality among HIV infected and HIV non-infected pregnant women. Methods- This retrospective, record-based, cohort study included 79 HIV infected and 79 HIV non-infected pregnant women, matched for 5 year age group and parity. Data was abstracted from medical records and analyzed using SPSS-18 software. Findings- Mean haemoglobin and weight prior to delivery was lower in exposed cohort (10.82 vs. 11.50 g%,p=0.011; 59.50 vs. 65.02 kgs; p=0.003 respectively). Exposed cohort had greater incidence of antenatal infections (12.70% vs. 3.80%, p=0.043), postpartum infections (19.10% vs 5.10%; p=0.007) and caesarean section (92.30% vs. 26.60%, p=0.000). Low birth weight was 2.74 times more common in neonates of HIV positive women (p=0.009). Neonatal hospitalization was longer (range: 3-58 vs. 1-51 days, median: 6 vs. 4 days; p=0.007) and neonatal complications were 3.95 times more common in the exposed cohort (p=0.007). Caesarean section and neonatal complications were independent risk factors associated with outcome of pregnancy in HIV positive women. Conclusion- A significant association exists between HIV infection and anaemia, antenatal and postpartum infections, lower maternal weight gain, caesarean section, low birth weight in neonate and duration of neonatal hospitalization.